2009
DOI: 10.1016/j.jcrs.2008.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Optical quality in eyes with aspheric intraocular lenses and in younger and older adult phakic eyes: Comparative study

Abstract: Spherical and coma aberrations were similar in eyes with an aspheric IOL and younger phakic eyes, although HOAs were higher in pseudophakic eyes. There were no differences between pseudophakic eyes and older phakic eyes in coma and HOA, although pseudophakic eyes had lower spherical aberration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
7
1
3
Order By: Relevance
“…Previous studies reported that in cataract-free eyes, the total HOA ranged from 0.27 to 0.58 μm, [16][17][18][19] coma from 0.14 to 0.21 μm, [20][21][22] and spherical aberration from 0.02 to 0.22. 16,18,20,[23][24][25][26] However, the total HOA (0.88, 1.22, and 1.31 μm) and coma (0.47, 0.67, 0.76 μm) were significantly increased in the good visual acuity cataract patients of our study compared with those in the cataract-free eyes of previous studies, [16][17][18][19][20][21][22] indicating visual deteriorations in these patients. Spherical aberrations of our patients were either more negative (−0.16 μm in the N group) or more positive (0.35 μm in C and N+C groups) than those of cataract-free eyes reported previously.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Previous studies reported that in cataract-free eyes, the total HOA ranged from 0.27 to 0.58 μm, [16][17][18][19] coma from 0.14 to 0.21 μm, [20][21][22] and spherical aberration from 0.02 to 0.22. 16,18,20,[23][24][25][26] However, the total HOA (0.88, 1.22, and 1.31 μm) and coma (0.47, 0.67, 0.76 μm) were significantly increased in the good visual acuity cataract patients of our study compared with those in the cataract-free eyes of previous studies, [16][17][18][19][20][21][22] indicating visual deteriorations in these patients. Spherical aberrations of our patients were either more negative (−0.16 μm in the N group) or more positive (0.35 μm in C and N+C groups) than those of cataract-free eyes reported previously.…”
Section: Discussioncontrasting
confidence: 78%
“…Spherical aberrations of our patients were either more negative (−0.16 μm in the N group) or more positive (0.35 μm in C and N+C groups) than those of cataract-free eyes reported previously. 16,18,20,[23][24][25][26] Internal aberrations may better represent the lens-induced changes, which were all significantly increased compared with the cataract-free eyes reported previously. [27][28][29] Thus, the relatively aggravated wavefront results might imply the Specific components of wavefront analysis may also predict specific visual complaints.…”
Section: Discussionmentioning
confidence: 64%
“…Patients with larger pupils seem to benefit more from aspheric IOLs under mesopic and scotopic conditions; however, elderly patients have a smaller pupil (senile miosis) than younger patients. 43,44 This may partly explain the lack of clinical benefit noted with an aspheric IOL in the older population. Another reason the benefits of aspheric IOLs are less than expected could be the Stiles-Crawford effect, which can minimize the effect of spherical aberration in eyes with a pupil larger than 4.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39] Computer eye models are an excellent tool to identify the relative contribution of different factors that affect optical quality in pseudophakic eyes, which is helpful to evaluate the real impact of new IOL designs and the potential need to improve cataract surgery.…”
Section: Intraocular Lens Alignment Rosales De Castro Jimenez-alfarmentioning
confidence: 99%